Kebijakan Hukum terhadap Tanggung Jawab Transnasional Corporations (TNCs) atas Pelanggaran Hak Menikmati Lingkungan yang Sehat di Indonesia - Sri Wartini; Jamaludin Ghafur (Fakultas Hukum Universitas Islam Indonesia, 2014)
The problems in this study, namely: first, how the policy of the law towards the responsibility of TNCs related to the violation of right of enjoying a healthy environment in Indonesia? Secondly, why the need for a model law policy against liability for infringement TNCs enjoyed a healthy environment in Indonesia? This research is normative. The approach used is the conceptual approach and legislation. Results of this study concluded that: first, the legal policy towards the responsibility of TNCs for violations of the right of enjoying a healthy living environment have not been explicitly included in the national regulations of Indonesia. Second, the model of law policy towards the responsibility of TNCs related to the violation of right of enjoying a healthy environment is necessary.